THE IMPLEMENTATION OF COLLABORATIVE STRATEGY READING (CSR) AND ITS EFFECTS ON STUDENTS’ READING COMPREHENSION - Indah Fadhilah Rahman (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aimed to find out: (1) the students’ attitude toward CSR in teaching-reading comprehension and (2) the role of CSR and its affects on students’ reading comprehension. This study was experimental which involved two groups: experimental and control groups. The research was conducted at Madrasah Aliyah Negeri MAN 1 Makassar, South Sulawesi with 40 students as respondents. The instruments of data collection were pre-test, treatment, post-test, and questionnaire. The reading test was administered to both groups. The scores were assessed by two assessors. The data were analyzed and interpreted by means of SPSS 14.0. The study reveals that the implementation of CSR has a significant effect on students’ reading proficiency in terms of content of the text: preview, clik and clunk, get the gist and wrap up. The results of students’ reading score from pre-test to post-test demonstrate a significant difference. It is found that sig. (2-tailed) is 0.000 lower than 0.05. The comparison of the students’ reading proficiency outcome between the two groups (8.592>2.024) shows that the improvement is significant. The finding signifies that CSR is positively responded by the experimental class. The implementation of CSR increases students’ reading proficiency.